Controlling Tautomerization in Pyridine‐Fused Phosphorus‐Nitrogen Heterocycles. Issue 22 (15th March 2022) - McNeill, J. Nolan; Karas, Lucas J.; Bard, Jeremy P.; Fabrizio, Kevin; Zakharov, Lev N.; MacMillan, Samantha N.; Brozek, Carl K.; Wu, Judy I.; Johnson, Darren W.; Haley, Michael M.
Abstract: Inclusion of a second nitrogen atom in the aromatic core of phosphorus‐nitrogen (PN) heterocycles results in unexpected tautomerization to a nonaromatic form. This tautomerization, initially observed in the solid state through X‐ray crystallography, is also explained by computational analysis. We prepared an electron deficient analogue (2 e ) with a fluorine on the pyridine ring and showed that the weakly basic pyridine resisted tautomerization, providing key insights to why the transformation occurs. To study the difference in solution vs. solid‐state heterocycles, alkylated analogues that lock in the quinoidal tautomer were synthesized and their different 1 H NMR and UV/Vis spectra studied. Ultimately, we determined that all heterocycles are the aromatic tautomer in solution and all but 2 e switch to the quinoidal tautomer in the solid state. Better understanding of this transformation and under what circumstances it occurs suggest future use in a switchable on/off hydrogen‐bond‐directed receptor that can be tuned for complementary hydrogen bonding. Abstract : This work reports the reproducible access to stable, nonaromatic PN‐heterocyclic quinoidal cores. The molecules exhibit solution and solid‐state λ max red‐shifts, and their solid‐state structures exhibit tautomer‐dependent hydrogen bonding.